Diagnostic efficacy of DIPSI criteria for diagnosis of gestational diabetes mellitus in comparison with WHO 2013 criteria - Yasmin, Sumaiya; Nasrin, Begum; Das, Tripti Rani; Mahmood, Sharmeen; Parvin, Maliha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational diabetes mellitus (GDM) is a global health issue due to its increasing prevalence and negative effects on maternal and fetal health. The standard screening method is the 75 g glucose tolerance test (OGTT), which requires fasting. The Diabetes in Pregnancy Study Group of India (DIPSI) suggests a one-stage, non-fasting test as an alternative, which could be more patient-friendly and aligns with international recommendations. This study aimed to assess the diagnostic efficacy of the DIPSI method compared to the WHO criteria for GDM screening. Methods: This cross-sectional study was conducted from October 2021 to September 2022 at the Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. One hundred and thirty-three singleton pregnant women who provided informed consent were included. Results: Among 133 participants, 34 (25.6%) were diagnosed with GDM according to WHO criteria, while 26 (19.5%) were diagnosed with DIPSI. The DIPSI method showed high specificity (96.97%) but lower sensitivity (67.65%) compared to the WHO criteria. The positive and negative likelihood ratios were 22.32 and 0.33, respectively, with an overall accuracy of 89.46%. Lowering the DIPSI cutoff to 7.3 mmol/L improved sensitivity to 82.4% and specificity to 92.9% and increased overall accuracy to 90.2%. Conclusions: The non-fasting DIPSI method demonstrated reasonable diagnostic accuracy compared to the WHO criteria. It is recommended for use in low-resource settings but should not replace the gold standard OGTT for comprehensive GDM screening.